By-wire cars turn the corner. - Bretz, E.A.
The basic concept of by-wire sounds simple enough: replace the car's mechanically linked hydraulic systems-steering and braking, for example-with electronic ones. By-wire systems began to be installed well over a decade ago, first in military and then in commercial aircraft. In a ?true? by-wire system, there would be no hydraulic backup to the electronic system; therein lies a cause for carmakers' concern. Drivers count on the fact that the brakes and steering work when and how they are supposed to, thanks to hydraulic systems. Car makers just don't know how drivers will react to the wires, computers, and microcontrollers. Another basic hurdle automakers face is that no industry-wide standard exists for a by-wire system. There is no set specification for the electronic control of a safety-critical system like braking or steering. While automakers agree that having such a standard will help both in winning public confidence in by-wire systems and in designing and implementing such systems, they have yet to agree on one. What's more, this standard needs to work for all safety-critical functions under the by-wire umbrella. This paper describes how by-wire systems work in aiding the driver in steering, stabilising and braking the car. The barriers to implementing such systems are outlined
Keywords: Braking; By-wire cars; Computers; Electronic systems; Industry-wide standard; Microcontrollers; Safety-critical system; Steering